Model Pembelajaran Komposisi Rampak Bedug Berbasis Kreativitas untuk Menaikkan Kemampuan Musikalitas Siswa SMP Negeri 1 Banjar Pandeglang - Muhammad Asegaf; Hadiyatno Hadiyatno; Syamsul Rizal (Indonesian Journal Publisher, 2026)
This study aims to improve students’ musicality skills through the implementation of a creativity-based Rampak Bedug composition learning model at SMP Negeri 1 Banjar Pandeglang. The background of this research stems from the low interest and musical abilities of students toward traditional arts due to conventional learning methods that limit creative expression. The research employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, action, observation, and reflection. The subjects were 30 eighth-grade students. Data were collected through observation, interviews, documentation, and performance assessments focusing on rhythm, dynamics, harmony, creativity, and coordination. The results showed a significant improvement across all aspects of musicality. The average score increased from 2.6 in Cycle I to 3.6 in Cycle II, with the highest gain in creativity (1.3 points). The model effectively enhanced students’ musical skills while fostering appreciation for traditional Rampak Bedug art. Through sound exploration, improvisation, and group collaboration, students became more active, confident, and creative in musical expression.